Development by Product of Mung Bean as Agroindustrial Product for Liquid Smoke and Charcoal Briquettes - Mahmudun Ainuri; N Fatmawati; F A Permana; A N Jatu (Agroindustrial Journal, 2021)
“Bakpia” is one of food agroindustrial products that use mung bean (Vigna radiata) as raw material. Mung bean peel waste is a source of organic materiali and available in abundance in Yogyakarta. One scenario to improve by-products of bakpia is utilize them as raw material of charcoal briquettes, as alternative energy and due to the decline of petroleum reserves and a dramatic explosion in demand for energy, and liquid smoke for food preservation. This study is conducted to evaluate the critical variables that effect on the production of liquid smoke and charcoal of mung bean peel waste on pyrolysis. This study converted by product of “bakpia” to high value product as liquid smoke and charcoal brequettes. To ensure its quality, pyrolysis process in difference in temperature and the time were conducted. Quality liquid smoke is determined by phenol content, acidity, and the pH value. The production of charcoal, pyrolysis treated in addition based on the temperature and duration of operation, also the weight ratio of the adhesive mixture and pressure. Quality parameters of charcoal briquettes based on physic-chemical properties, namely: water content, ash content, volatile content and calorific value assessed, bound-carbon content, density, and performance of combustion. Besides the technical criteria, financial aspects also be taken into consideration their financial feasibility such as; NPV, IRR, PBP and PI. It was found that charcoal production of mung beans peel waste based on temperature and the duration of the pyrolysis 400 °C for 3 hours, with the results of 7.31 % water content , 22.21 % ash content, 57.03 % volatile compound , and 6696,041 cal/g calorific value. Charcoal Quality obtained at 5 % the amount of adhesive, 50 Kg/m2 pressure of pressing, which 4.93 % of ash content, 14.84 % volatile content, 6188.53 cal/g calorific value, 76.37 % bound carbon content, and has a density of 0.63 g/cm3. The performance of combustion, reached in 6th minute and longer burning flame. The financial feasibility of charcoal briquettes and liquid smoke of mung beans peel waste produce PBP of 1.12 years, NPV of IDR 35,947,702, - IRR of 73.6% and PI of 5.15.